PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KOTA SEMARANG - Nia Vitha Syara, 14.05.51.0004; Kasmari, Kasmari (Students' Journal of Economic and Management, 2018)
Abstract This study aims to analyze the influence of Motivation, Work Environment, and Competence on Employee Performance Social Office Semarang City. The population in this study is the total number of employees amounted to 45 respondents. The data used are primary data, that is data obtained directly from the source. The technique used for primary data collection is done by means of questionnaires to the respondents. The test of determination (R²) indicate that employee performance can be explained by Motivation, Work Environment, and Competenceh of 57,7%, while the remaining is influenced by other variables outside of research. The f test indicate that Motivation, Leadership and Work Environment jointly significant effect on employee performance. The t test indicate that Motivation has a positive and significant impact on employee performance, work environment has a positive and significant impact on employee performance, Competence has a positive and significant impact on employee performance.Keywords: Motivation, Workplace Environment, Competence and Employee Performance.